2021
DOI: 10.3390/ijms22189910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous pH on Cell Growth of Breast Cancer Cells

Abstract: Breast cancer is the most common type of cancer in women and the most life-threatening cancer in females worldwide. One key feature of cancer cells, including breast cancer cells, is a reversed pH gradient which causes the extracellular pH of cancer cells to be more acidic than that of normal cells. Growing literature suggests that alkaline therapy could reverse the pH gradient back to normal and treat the cancer; however, evidence remains inconclusive. In this study, we investigated how different exogenous pH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…It shows that the extracts of strains LB3 and LB5 have high cytotoxicity on Caco-2 cells with IC50 40.8 and 51 µg/mL, respectively. Cancer cells have a lower extracellular pH of 6.7-7.1 and a higher intracellular pH of 7.4, whereas normal cells have a higher extracellular pH of 7.4 and a lower intracellular pH of 7.2(Lee and Shanti, 2021).Li et al…”
mentioning
confidence: 99%
“…It shows that the extracts of strains LB3 and LB5 have high cytotoxicity on Caco-2 cells with IC50 40.8 and 51 µg/mL, respectively. Cancer cells have a lower extracellular pH of 6.7-7.1 and a higher intracellular pH of 7.4, whereas normal cells have a higher extracellular pH of 7.4 and a lower intracellular pH of 7.2(Lee and Shanti, 2021).Li et al…”
mentioning
confidence: 99%
“…Lee et al demonstrated that medium alkalinity resulted in a combination of effects in MDA-MB231 cells, retardation of cellular growth, induction of cell death via necrosis and apoptosis, and a shift in the cell cycle away from the G0/G1 phase. On the other hand, slightly acidic conditions increased cellular growth and did not cause significant cell death . Within the same context, after 48 h culture of human CD24-/CD44+ breast cancer stem cells, the growth rate was slower (13.3 × 10 5 viable cells) when compared to the nonalkalinized culture (25.2 × 10 5 viable cells) …”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, slightly acidic conditions increased cellular growth and did not cause significant cell death. 48 Within the same context, after 48 h culture of human CD24-/CD44+ breast cancer stem cells, the growth rate was slower (13.3 × 10 5 viable cells) when compared to the nonalkalinized culture (25.2 × 10 5 viable cells). 49 Additionally, FACS analysis also revealed that that when cultured in the presence of BrCr Pt serum, MCF-7 cell apoptosis is diminished relative to FBS and serum from HV (Figure 2B,C).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Thus, the pH effect on the drug release rate is associated with an increase in the proportion of non-immobilized doxorubicin in the salt (in an acidic medium) or basic form (in an alkaline medium). On the other hand, it is known that cancer cells are often characterized by a lower pH value compared to normal cells [ 58 , 59 ]. However, the main difference between cancer cells and normal cells is the high intensity of metabolic processes and an increased rate of endocytosis, which is realized through specific mechanisms such as macro-pinocytosis [ 60 ].…”
Section: Resultsmentioning
confidence: 99%